The Effect of a Mannanoligosaccharides (Biomos®) on Necrotic Enteritis Infection in Broiler Chickens - Mohamed, Moemen A.; Hafez, Mohamed S. Abdel (International Journal of Poultry Science, 2011)
This study was conducted to determine the effect of Mannanoligosaccharide (Biomos®, Alltech Inc., IFT, Egypt) added to a broiler ration to reduce or control the prevalence of necrotic enteritis among broiler chicks reared under normal conditions. Seventy five, one-day-old, Cobb chicks were randomly divided to three groups of 25 birds for each. First group consists of nonchallenged negative control group, second group was a positive control group gavaged with C. perfringens (CP) (107 cfu/mL) daily for 3 consecutive days starting on d 16. The third group was supplemented with 2 g/kg ration from the start to the end of the experiment and orally challenged with C. perfringens type A at the the same method for positive control group. On days 1 (19-day-old) and 7 (25-day-old) post-challenge, lesion scores, mortalities and intestinal CP levels were assessed. The log10 C. perfringens/g of intestinal contents was significantly reduced in the biomos treated group (MTG) with a log10 value of 1.8 and 2.2 at the 1st and 7th days after challenge respectively compared with 4.3 and 4.7 at the same times respectively in the Positive Control Group (PC). Mortality was reduced to 8% in group supplemented with Biomos in contrast to 20% in positive control group. The present study revealed that the birds given biomos supplementation showed a reduction in the severity of lesion score which reached to 0.57 in contrast to 1.8 in positive control group. In summary, the findings of the present study strengthen the use of biomos as a safe alternative to antibiotics and attractive aid for prevention and control of Clostridium perferingens infections in broilers.